Fabrication and Characterization of DNA Sensors from Metal Oxides Nanoparticles and Chitosan-Modified Glassy Carbon Electrodes - Mohd Maamor, Nor Amirah (2011)
Voltammetric studies of a sensitive electrochemical deoxyribonucleic acid (DNA) sensor based on nano particles and multi-walled carbon nanotube (MWCNTs) for DNA immobilization is described. In this study, two nanoparticles were used, zirconium oxide (ZrO2) and titanium oxide (TiO2). Layer deposition technique was used to prepare nanoparticles/MWCNTs/chitosan (CHIT)-modified glassy carbon electrode (GCE) and DNA were immobilized to the GCE. The immobilization of DNA on the electrode was monitored by cyclic voltammetry (CV) analysis by measuring the change of peak currents using electroactive methylene blue (MB) as an indicator. Compared with previous DNA sensor with DNA directly incorporated on carbon electrodes, this carbon nanotube-based assay with its large surface area and good charge-transport characteristics increased DNA attachment quantity. Parameters used on this study including electrochemical characterization, scan rate study and pH optimization as well as chronoamperometry (CA) and chronocoulometry (CC). The electrochemical reduction and oxidation of the redox couples of MB (as a DNA indicator) can be recognized easily by the solid-phase voltammetry of nanoparticles. The cyclic voltammograms for the three differently modified electrodes, nanoparticles/CHIT, MWCNTs/CHIT and nanoparticles/MWCNTs/CHIT, showed that there are 2 major peaks due to the redox couple of MB. Electrochemical characterization of the two modified electrodes, nanoparticles/MWCNTs/CHIT, shows that both of this modified electrode give highest peak current, evident that the composite mixtures cause the increase in the redox peak current of MB. For hybridization study, the current enhancement observed in three differently fabricated DNA sensor based on DNA/TiO2/CHIT/GCE, DNA/MWCNTs/CHIT/GCE and DNA/TiO2/MWCNTs/CHIT/GCE, responding to redox couple of MB are compared. The sensor DNA/TiO2/MWCNTs/CHIT/GCE was found to the most be sensitive towards hybridized DNA. Parameters, used in this study include hybridization time, hybridization temperature, accumulation time, effect of varying concentration of probe, calibration curve, selectivity of DNA sensor, reproducibility and repeatability. From the studies, the optimized condition of hybridization for target ssDNA reaching the ssDNA probe is 30 min at 30 oC. The accumulation time of MB, time taken for MB to bind with dsDNA is 150 seconds, while, 100 μM of ssDNA probe was found to be the appropriate dosage for the fabrication of the sensor